Aluminum doped zinc oxide nanoplatelets based sensor with enhanced hydrogen sulfide detection - Brahim Ydir; Amine Ajdour; Iulia Antohe; Gabriel Socol; Marcela Socol; Luiza-Izabela Toderascu; Driss Saadaoui; Imade Choulli; Radouane Leghrib; Houda Lahlou (Scientific Reports)
Abstract This study explores the development of highly sensitive hydrogen sulfide (H2S) gas sensors employing hierarchical aluminum-doped zinc oxide (AZO) nanostructures. Vertically oriented AZO nanoplatelets with Al/ZnO molar ratios of 4% and 6% were successfully synthesized using an automated successive ionic layer adsorption and reaction (SILAR) technique. The morphological features of the AZO films significantly changed with the Al content. The AZO thin films exhibited a polycrystalline wurtzite structure and an increase in crystallite size with increasing Al concentrations. This work demonstrates that our AZO sensor structures achieved a maximum response at 150 ppm H2S and 573 K of 23.3%, being characterized by fast response and recovery times of 28 and 464 s, respectively. Notably, the 6% AZO samples exhibited an augmented selective sensitivity to H2S, demonstrating stable detection performance. Additionally, the significant improvement in detection capabilities can be attributed to the synergistic effects of electronic and chemical sensitization. These effects enhance the formation of active sites and create doping-induced defects while providing shorter and more efficient diffusion paths for the electrons, significantly improving the sensor’s sensitivity and response speed.